POLYMER TYPE EFFECT ON PREMNA SERRATIFOLIA EXTRACT-LOADED MICROPARTICLES PREPARATION BY SOLVENT EVAPORATION METHOD WITH SINGLE EMULSION SYSTEM - NURHASANAH, SITI; ISKANDAR, YOPPI; MUHAIMIN, MUHAIMIN; HAZRINA, AGHNIA; HIRZAN, RIFANZA; SYAHRI, WILDA (International Journal of Applied Pharmaceutics, 2024)
Objective: Premna serratifolia linn leaf possesses medicinal properties, useful in the treatment of cardiovascular diseases, skin diseases, inflammatory diseases and arthritis. P. serratifolia leaves extract was easy to damage because the light exposure, change of pH, weather and a long period of storage time. The problem can be solved by preparation the extract with microparticle technique. The purpose of this research was to formulate the microparticles of P. serratifolia leaves extract with solvent evaporation technique using Ethocel 10 cP and Eudragit E100 as matrix. Methods: P. serratifolia leaves were extracted using ethanol 70%. This extract was dried by rotary evaporator. The microparticle process of P. serratifolia leaves extract was done by solvent evaporation technique (O/W: oil in water). The formula of P. serratifolia leaves extract microparticles was designed into six formulas (Ethocel 10 cP: EA1, EA2, EA3 and Eudragit E100: EB1, EB2, EB3 (10%,15%, 20%)), that they were dissolved in dichloromethane. Microparticles of P. serratifolia leaves extract were characterized for particle size in terms of surface morphology by scanning electron microscope (SEM) and encapsulation efficiency. Results: In this research, the micoparticles containing P. serratifolia extract has been developed by using ethyl cellulose (Ethocel 10 cP) and eudragit (Eudragit E100) as the polymer matrix. The results showed that high concentration of polymer (Ethocel 10 cP (20%)) used in microparticles resulted in better P. serratifolia leaves extract microparticles in terms of physical characteristics. Particle size of microparticles containing P. serratifolia leaves extract were in the range of 1.024 to 1.662 μm. Encapsulation efficiency (% EE) was categorized as good because the value were ≥ 80% to, which 83.101% (EB3) and 85.574% (EA3). SEM picture of EA3 (Ethocel 10 cP) revealed that the surface of microparticles were a smoother surface and less visible pores of microparticles were obtained. When Eudragit E100 used as polymer, a rough and porous surface of microparticles were obtained. Conclusion: It can be concluded that microparticles of P. serratifolia leaves extract can be prepared by solvent evaporation method with a single emulsion system (O/W) using Ethocel 10 cP and Eudragit E100 as polymer. Characterization of the microparticles revealed that polymer type used on this method is applicable to produce microparticles.